2014
DOI: 10.1080/13602381.2014.950056
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the role of Chinese workers in problem solving: a study of transformational leadership, trust and security in ‘lean’ manufacturing

Abstract: In this paper, we study leadership style and organizational culture, elements that, we argue, are conducive for Chinese shop-floor employees to participate in problem solving in 'lean' manufacturing. Power distance and the concern for saving face potentially hinder employees' willingness to participate in such problem solving, but our findings support the notion that transformational leadership helps to overcome these barriers. The relationships are not straightforward, however, and by examining the complexiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…cost, speed, dependability, quality and flexibility Belekoukias et al (2014) Investigating the network of influences among lean practices (supplier management, human resource management, just-in-time and total quality management practices), operational responsiveness (product mix variety, product innovation and time effectiveness) and company growth performances in Italian companies Bevilacqua et al (2017) Modelling of job design under lean manufacturing to capture the distinct motivational and health-impairing potential Cullinane et al (2014) Exploring the CSFs, i.e. the critical success factors for Lean Six Sigma in the Malaysian automotive industry Fadly Habidin and Mohd Yusof (2013) Examining how utilization of non-financial manufacturing performance (NFMP) measures impacts the LM and financial performance relationship Fullerton and Wempe (2009) Study on how lean management accounting practices can support operations personnel with their internal decision making, and operations executives and business leaders in their objective of increasing lean operations performance as part of a holistic lean enterprise strategy Fullerton et al (2014) Examining whether application of information technology and different principles of LM are interdependent and complimentary or they are mutually exclusive Ghobakhloo and Hong (2014) Investigating the degree to which LM practices are being implemented within Brazilian small and medium enterprises (SMEs), by defining what LM means, in the view of SMEs in Brazil Godinho Filho et al (2016) Investigating the unique and complementary effects of manufacturing technologies and lean practices on operational performance of manufacturing firms Khanchanapong et al (2014) Exploring the relationship between a firm's competitive strategy and its operations practices consistent with the adoption of LM Laosirihongthong et al (2010) Study on leadership style and organizational cultureelements that are conducive for Chinese shop-floor employees to participate in problemsolving in LM Li et al (2015) Study of the effect of employee involvement on LM and the effect of LM on production outcomes Marin-Garcia and Bonavia (2015) Examining the relationship among lean manufacturing management, competitive skills, and business performance from the perspective of managers of companies doing business in Brazil Moori et al (2013) Providing an outline of lean implementation helping managers to implement lean in their premises and using SEM to develop independent and latent variables Ravikumar et al (2013) Developing a model for measuring adherence to lean practices for automotive part suppliers and assessing the relationship between the firm performance and the adoption of lean principles Sezen et al (2012) Providing guidance for the management of supply chains in order to increase the likelihood of lean thinking being generally adopted for the purposes of value creation, and exami...…”
Section: Authorsmentioning
confidence: 99%
“…cost, speed, dependability, quality and flexibility Belekoukias et al (2014) Investigating the network of influences among lean practices (supplier management, human resource management, just-in-time and total quality management practices), operational responsiveness (product mix variety, product innovation and time effectiveness) and company growth performances in Italian companies Bevilacqua et al (2017) Modelling of job design under lean manufacturing to capture the distinct motivational and health-impairing potential Cullinane et al (2014) Exploring the CSFs, i.e. the critical success factors for Lean Six Sigma in the Malaysian automotive industry Fadly Habidin and Mohd Yusof (2013) Examining how utilization of non-financial manufacturing performance (NFMP) measures impacts the LM and financial performance relationship Fullerton and Wempe (2009) Study on how lean management accounting practices can support operations personnel with their internal decision making, and operations executives and business leaders in their objective of increasing lean operations performance as part of a holistic lean enterprise strategy Fullerton et al (2014) Examining whether application of information technology and different principles of LM are interdependent and complimentary or they are mutually exclusive Ghobakhloo and Hong (2014) Investigating the degree to which LM practices are being implemented within Brazilian small and medium enterprises (SMEs), by defining what LM means, in the view of SMEs in Brazil Godinho Filho et al (2016) Investigating the unique and complementary effects of manufacturing technologies and lean practices on operational performance of manufacturing firms Khanchanapong et al (2014) Exploring the relationship between a firm's competitive strategy and its operations practices consistent with the adoption of LM Laosirihongthong et al (2010) Study on leadership style and organizational cultureelements that are conducive for Chinese shop-floor employees to participate in problemsolving in LM Li et al (2015) Study of the effect of employee involvement on LM and the effect of LM on production outcomes Marin-Garcia and Bonavia (2015) Examining the relationship among lean manufacturing management, competitive skills, and business performance from the perspective of managers of companies doing business in Brazil Moori et al (2013) Providing an outline of lean implementation helping managers to implement lean in their premises and using SEM to develop independent and latent variables Ravikumar et al (2013) Developing a model for measuring adherence to lean practices for automotive part suppliers and assessing the relationship between the firm performance and the adoption of lean principles Sezen et al (2012) Providing guidance for the management of supply chains in order to increase the likelihood of lean thinking being generally adopted for the purposes of value creation, and exami...…”
Section: Authorsmentioning
confidence: 99%
“…Employee participation can be viewed as a "ladder" ranging from no power given to the employees to models where large amount of control is delegated (Li et al, 2015). Participation and involvement can potentially benefit both workers and firms (Heller et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Employees who are involved in making decisions that influence them during the planning process by generating alternatives and evaluating consequences tend to be more satisfied and engaged. When they are given greater control over their work lives, employees are more eager to apply their skills and knowledge, share information (Li et al, 2015) and are less likely to look for other job opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…The authors identified corresponding leadership styles that were mentioned in previous studies of leadership literature, see table 1. [23], [63], [24], [64], [65], [66], [67] Transformational leadership [63], [68], [65], [69], [70], [71] Servant leadership [63], [68], [72], [73] Authentic leadership [63], [55] Empowering leadership [21], [68], [74], [75], [29] Distributed leadership (Team leadership) [63], [70] The following paragraphs are provided clarification for the impact of those leadership styles on Lean Six Sigma implementation success. The organisations are thinking about using Lean Six Sigma, can pay attention to the behaviours and attitudes of the leaders associated to these styles.…”
Section: Resultsmentioning
confidence: 99%